2015
DOI: 10.1080/02723638.2015.1049480
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gentrification on residential evictions

Abstract: Gentrification, a process of transforming working-class areas into middle-class use, is a pervasive process in many cities around the world. Although researchers recognize the dangers of displacement in this process, the magnitude of dislocation is highly contested. Literature on gentrification offers little guidance with regard to understanding the timing of displacement in a gentrifying neighborhood. Moreover, evictions have been neglected as a form of gentrification-led displacement, which may have led to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…This is an important gap in current knowledge given the documented association between unstable housing and exposure to violence among PWID (Marshall et al, 2008; Wenzel et al, 2001; Wenzel et al, 2004b), and given evidence suggesting that housing displacement may have health and social impacts distinct from those related to homelessness (Cooper et al, 2012; Desmond & Kimbro, 2015; Kennedy et al, 2016; Pollack & Lynch, 2009). Moreover, residential eviction is common among PWID, particularly among those living in inner-city neighbourhoods characterized by ongoing gentrification and redevelopment (Chum, 2015; Kennedy et al, 2016). One such neighbourhood is Vancouver’s Downtown Eastside (DTES), a postindustrial area marked by an open drug market, poverty and increasing levels of homelessness and housing instability (Kennedy et al, 2016; Sutherland, Swanson & Herman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important gap in current knowledge given the documented association between unstable housing and exposure to violence among PWID (Marshall et al, 2008; Wenzel et al, 2001; Wenzel et al, 2004b), and given evidence suggesting that housing displacement may have health and social impacts distinct from those related to homelessness (Cooper et al, 2012; Desmond & Kimbro, 2015; Kennedy et al, 2016; Pollack & Lynch, 2009). Moreover, residential eviction is common among PWID, particularly among those living in inner-city neighbourhoods characterized by ongoing gentrification and redevelopment (Chum, 2015; Kennedy et al, 2016). One such neighbourhood is Vancouver’s Downtown Eastside (DTES), a postindustrial area marked by an open drug market, poverty and increasing levels of homelessness and housing instability (Kennedy et al, 2016; Sutherland, Swanson & Herman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging body of work has investigated the relationship between evictions and gentrification. For example, in his study of evictions data in Toronto, Canada, Chum (2015) found that there is a significant relationship between gentrification and evictions, and his findings suggest that "excluding evictions in the study of gentrification may lead to the underestimation of displacement effects" (p. 1092). Further, he found that the timing of gentrification was an important factor in this relationship.…”
mentioning
confidence: 99%
“…In other words, there is no single answer on whether gentrification is a universal tool in the implementation of urban policy or not (Chum, 2015).…”
Section: Discussion and Resultsmentioning
confidence: 99%